Hubungan antara tahap kompetensi dengan tahap prestasi kerja di kalangan pentadbir Kolej Universiti Teknologi Tun Hussien Onn (KUiTTHO) - Md Salleh, Shamsulkhairi (2006)
This research is a case research in studying the connection of competency level with the administrator in Kolej University Teknologi Tun Hussein Onn (KUiTTHO). Research was done on 40 respondents which were identified playing an important role in giving the feedback. All the respondents are a public service officer from the management and professional group in KUiTTHO, Batu Pahat, Johor. Results from the research are gathered using the Statistical Package for Social Sciences (SPSS version 13.0) software. Model for the Managers Competency and KUiTTHO Annual Assessment Report Form are the main components in the establishing the research framework. As for the independent variable, competencies are divided into four clusters which is personal management, group management, working management and collaborative management. While the dependent variable which is job performance is divided into three dimensions which are working result, knowledge and ability and personal quality. Throughout the research the result shows that the competency level and job performance level for the KUiTTHO administrator are at the highest level. Based on Pearson correlation analysis, research result shows that the positive relationship exists is at the average level. However, competency levels are still playing a huge role in increasing the level of the administrator job performance in KUiTTHO.